Dramaturgy remaja di media sosial - Ramli, Romlah (Universiti Tun Hussein Onn Malaysia Publisher’s Office, 2019)
This paper describes the 'Dramaturgy' Model with the use of social media as a communicative platform into categories of roles that are to be featured on the social media platform, characters that are featured on social media, factors in the process of acting on social media and preparation for communicating in the media social. The research method used was through interviews with nine informants who are users of social media. In general, based on the 'dramaturgy' model, there are three aspects that are emphasized in the role of the show, the characters that are featured on social media, the factors involved in the process of acting on social media and also the preparation for communicating on social media. For their role in the show, social media users stated that they were honest, interested, self-satisfied and some even claimed they were not transparent in the media. In terms of personality, it was found that the characters displayed on social media were as diverse, cheerful, funny, eloquent, engaging, neutral, carefree, friendly and relaxed.